2021
DOI: 10.1186/s12916-021-02109-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of methylation signatures in circulating cell-free DNA for early detection of esophageal cancer: a case-control study

Abstract: Background Plasma cell-free DNA (cfDNA) methylation has shown promising results in the early detection of multiple cancers recently. Here, we conducted a study to investigate the performance of cfDNA methylation in the early detection of esophageal cancer (ESCA). Methods Specific methylation markers for ESCA were identified and optimized based on esophageal tumor and paired adjacent tissues (n = 24). Age-matched participants with ESCA (n = 85), ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…They tested the model in three independent cohorts and achieved good sensitivities (74.7%–86.0%) and specificities (94.0%–95.9%) ( Qiao et al, 2021 ). However, the sensitivity of this diagnostic model for stage 0-II esophageal cancer was only 58.8% ( Qiao et al, 2021 ).…”
Section: Dna Methylation In Bloodmentioning
confidence: 99%
“…They tested the model in three independent cohorts and achieved good sensitivities (74.7%–86.0%) and specificities (94.0%–95.9%) ( Qiao et al, 2021 ). However, the sensitivity of this diagnostic model for stage 0-II esophageal cancer was only 58.8% ( Qiao et al, 2021 ).…”
Section: Dna Methylation In Bloodmentioning
confidence: 99%
“…More recently, some studies have demonstrated the clinical value of circulating tumor DNA (ctDNA) for EC [ 11 , 12 ]. The ctDNA is defined as cell free DNA (cfDNA) released by necrotic and apoptotic cancer cells into the blood; and its diagnostic, therapeutic, and prognostic value have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is among the leading causes of cancer-related deaths worldwide [ 1 , 2 , 3 ]. The current mainstream treatments for esophageal cancer include esophagectomy, chemotherapy, radiotherapy, targeted therapy, multimodal therapy and recently, immunotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%